Minimize of Error Estimation and Approximate Solution of Fifth OrderInitial Value Problems - Hama-Salh, Faraidun K.; Salih, Dhuha M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
In this paper, we derive some difference schemes for the initial value problems using approximate spline interpolation, with the sixth degree lacunary spline function that interpolates the solution function of the problem; first and fourth order accurate schemes are obtained. To test the efficiency of the method, several numerical examples of third and fifth order initial value problems are solved by proposed method.
Keywords: Differential equations; Spline interpolation; Absolute error; Lipchitz condition